2007
DOI: 10.1177/0363546506293900
|View full text |Cite
|
Sign up to set email alerts
|

Head, Face, and Eye Injuries in Scholastic and Collegiate Lacrosse

Abstract: Although permitting only incidental contact, women's lacrosse had higher rates of head, face, and eye injuries at both the high school and collegiate levels. Concussion was the most common injury. For men, the primary injury mechanism was player-to-player contact; women's injuries primarily resulted from stick or ball contact. High school injury rates were lower than were college rates, but the nature of injuries, body parts affected, and mechanisms were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 11 publications
3
70
2
Order By: Relevance
“…Rugby, ice hockey, and lacrosse also account for higher rates of concussions but are often club sports, which limits their data inclusion in the larger high school sports epidemiologic studies. [34][35][36][37] …”
Section: Epidemiology Of Concussionmentioning
confidence: 99%
“…Rugby, ice hockey, and lacrosse also account for higher rates of concussions but are often club sports, which limits their data inclusion in the larger high school sports epidemiologic studies. [34][35][36][37] …”
Section: Epidemiology Of Concussionmentioning
confidence: 99%
“…Scientific interest in the problem of lacrosse-related injuries has also grown in recent years, although a few prospective epidemiological studies have been conducted (Diamond & Gale, 2001;Dick et al, 2007a;Dick, Romani, Agel, Case, & Marahall, 2007b;Hinton, Lincoln, Almquist, Douoguih, & Sharma, 2005;Lapidus, Nelson, Jeffers, Kay, & Schwarz, 1992;Lincoln, Hinton, Almquist, Lager,: & Dick, 2007;Livingston & Forbes, 1996;Matz & Nibbelink, 2004;Mayer, Kenney, Edlich, & Edlich, 1987;Waicus & Smith, 2002;Webster, Bayliss, & Spadaro, 1999;Yard & Comstock, 2006). Previous research has found that the location, type and mechanisms of injuries in lacrosse players vary by gender, mainly due to the inherent differences in the nature of men's and women's lacrosse.…”
Section: Introductionmentioning
confidence: 99%
“…Most game injuries in collegiate women resulted from non-contact (Dick et al, 2007a(Dick et al, , 2007b. Women were found to have higher rates of head, face and eye injury than men at both the highschool and collegiate levels (Lincoln et al, 2007). Also, at the collegiate level, concussions most often occurred in women while they were involved in passing or catching the ball and in men while they were pursuing loose balls (Hinton et al, 2005;Lincoln et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This has also been seen in experimental concussion in an animal model accompanied by axonal injury [48,49]. During the phase of recovery, the concussed brain is at risk for greater damage with a repeat blow [50,51]. Cases of increased dysfunction and disability after a second concussion are also seen in young children and adolescents [48,49].…”
Section: Traumatic Brain Injurymentioning
confidence: 86%